-17-20=-13x+80

Simple and best practice solution for -17-20=-13x+80 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17-20=-13x+80 equation:


Simplifying
-17 + -20 = -13x + 80

Combine like terms: -17 + -20 = -37
-37 = -13x + 80

Reorder the terms:
-37 = 80 + -13x

Solving
-37 = 80 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
-37 + 13x = 80 + -13x + 13x

Combine like terms: -13x + 13x = 0
-37 + 13x = 80 + 0
-37 + 13x = 80

Add '37' to each side of the equation.
-37 + 37 + 13x = 80 + 37

Combine like terms: -37 + 37 = 0
0 + 13x = 80 + 37
13x = 80 + 37

Combine like terms: 80 + 37 = 117
13x = 117

Divide each side by '13'.
x = 9

Simplifying
x = 9

See similar equations:

| 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 | | 3m+167=55+4m | | 12y+22=9y | | 3x(x+20)=44 | | -11+8x=-67 | | -2p+28=6p-44 | | -6(x+2)-13=10+1 | | (-10x+35)*(5)=x | | 9t=42 | | 9(-8)-4((-8)-7)= | | -2x+7+7x=-3 | | -65+2x=33-5x | | 7c-4c=78+12 | | 34-5x=-21 | | 6y-90=5y-75 | | 5(t-6)+5t=5(2t+2)-9 | | (-10x+35)*(5)= | | (6-2c)+(3c-4)= | | 0.5+0.7=-0.75 | | 4h=5h-60 |

Equations solver categories